Water balance of selected postmining reservoirs in the Łęknica Region = Bilans wodny wybranych zbiorników poeksploatacyjnych w rejonie Łęknicy - Kołodziejczyk, Urszula; Asani, Anna; Byszkiewicz, Marta; Jędrzejczyk, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of the hydrological balance calculated for selected anthropogenic reservoirs and their drainage basins, which are located in the southwestern part of the Lubuski District, and were created as a result of brown coal mining. The purpose of this work is the quantity evaluation of the diversification of water balance components and their influence on the quality of the environment.
Keywords: bilans wód; zbiorniki pogórnicze; pojezierze antropogeniczne; hydrological balance; post-mining reservoirs; anthropogenic lakeland